Estágio supervisionado obrigatório urolitíase canina: relato de caso - Félix, Natanael Silva (Universidade Federal Rural do Semi-Árido, 2021)
The internship is an opportunity for the student, as it allows them to experience the environment and routine that figure in their future activity, in addition to being able to monitor and carry out procedures, under the supervision of a professional. The objective of the work is to report a case of canine urolithiasis, as well as describe the activities performed during the internship period. Uroliths are formed from the separation of minerals present in urine, which can join an organic or mineral matrix, in the absence of urinary concretion inhibitors. A predisposition to the formation of uroliths is multifactorial, with the lower urinary tract being the place where more uroliths are found, specifically in the bladder. Small dogs are usually the most affected. The most commonly found uroliths are struvite, calcium oxalate, calcium phosphate, ammonium urate, cystine and silica. A two-year-old male Shih Tzu canine was seen at the Petshop Pet.com, who had anuria and stranguria for a few days with abdominal sensitivity. Laboratory and imaging tests were requested. An ultrasound revealed calculi adhered to the uroepithelium and signs of cystitis. Two stones were expelled by urohydropropulsion. Clinical signs are related to the urinary system. Diagnosis is made through anamnesis, clinical signs, laboratory and imaging tests. Treatment can be clinical or surgica
Keywords: Urolitíase; Urólitos; Urina; Bexiga; Uretra; CIENCIAS AGRARIAS::MEDICINA VETERINARIA